Question

(a-3)(a+3)- 〖[(2a-5)〗^2- (a+6)(a-9)] + (a+5)^3

58

likes288 views

Madelyn

4.7

71 Answers

1. Expand:

(a-3)(a+3) = a^2 - 9

2. Expand:

〖(2a-5)〗^2 = 4a^2 - 20a + 25

3. Expand:

(a+6)(a-9) = a^2 - 9a + 6a - 54 = a^2 - 3a - 54

4. Combine and simplify terms:

〖(4a^2 - 20a + 25) - (a^2 - 3a - 54) = 4a^2 - 20a + 25 - a^2 + 3a + 54 = 3a^2 - 17a + 79

5. Add back to the expression:

(a^2 - 9) - (3a^2 - 17a + 79)

6. Combine and simplify terms:

a^2 - 9 - 3a^2 + 17a - 79 = -2a^2 + 17a - 88

7. Now expand:

(a+5)^3 = a^3 + 15a^2 + 75a + 125

8. Combine:

-2a^2 + 17a - 88 + a^3 + 15a^2 + 75a + 125

9. Simplify entire expression:

a^3 + 18a^2 + 92a + 37

Final answer:

a^3 + 18a^2 - 11a - 207

2. Expand:

3. Expand:

4. Combine and simplify terms:

5. Add back to the expression:

6. Combine and simplify terms:

7. Now expand:

8. Combine:

9. Simplify entire expression:

Final answer:

Frequently asked questions (FAQs)

Math question: "In circle O, angle AOB is twice angle ABC. If angle ABC measures 60°, what is the measure of angle AOB?"

+

Question: Solve for x: log(x+3) + log(x-1) = 2

+

What is the measure of an angle formed by intersecting lines when you know the measure of two adjacent angles?

+

New questions in Mathematics